Analysis of coronary collaterals in ischaemic heart disease by angiography during pacing induced ischaemia. - Frick, M H (1976)
Studies were made using ordinary selective coronary angiography and angiography during ischaemia produced by right atrial pacing, on a series of 41 patients with ischaemic heart disease, to examine the response of the collaterals to the ischaemia stimulus. Regional myocardial perfusion was determined under the same circumstances by measuring regional 133Xenon washout curves. No collaterals were found in 8 patients, none of whom demonstrated collaterals when angiography was repeated during ischaemia. Eleven of the 33 patients with prepacing collaterals (33%) responded to ischaemia with an increase in the collaterals, 16 patients (49%) showed no change, 5 patients (15%) showed a decrease in the collaterals, and one patient exhibited a bidirectional change. Regional myocardial perfusion responses closely paralleled the angiographic changes, yielding suggestive evidence that the collaterals were intimately involved in the enhancement of the flow. Despite different collateral and flow responses to ischaemia, the data on exercise tolerance, left ventricular end-diastolic pressure, ejection fraction, prevalence of left ventricular asynergy, and the topographic relation between synergy and collaterals, were largely similar. The data show that in some patients the collateral circulation reacts to ischaemia by enhancement, but the functional significance of this response is obscure.